2018
DOI: 10.1111/age.12699
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in fat‐ and short‐tailed sheep from high‐throughput RNA‐sequencing data

Abstract: The identification of genetic variations underlying desired phenotypes is one of the main challenges of current livestock genetic research. High-throughput transcriptome sequencing has been recognized as an efficient way to unravel the rich genetic variants across various species. The Lanzhou Fat-Tail sheep is an endangered sheep breed in China with a notable feature of an exaggerated fat tail that also independently occurs in other sheep breeds. However, the genetic mechanism underlying this particular trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…However, under the hypothesis that the important genes/genomic regions related to fat-tail formation are evolutionarily conserved among different sheep breeds, we took into account the common SNPs/genes or genomic regions with previous similar studies. In total, 300 SNPs (78 SNPs in Lori-Bakhtiari and 222 SNPs in Zel) were concordant with previous studies on sheep breeds 6 , 8 , 44 . These SNPs were located within 91 genes (Supplementary File S1 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, under the hypothesis that the important genes/genomic regions related to fat-tail formation are evolutionarily conserved among different sheep breeds, we took into account the common SNPs/genes or genomic regions with previous similar studies. In total, 300 SNPs (78 SNPs in Lori-Bakhtiari and 222 SNPs in Zel) were concordant with previous studies on sheep breeds 6 , 8 , 44 . These SNPs were located within 91 genes (Supplementary File S1 ).…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study, transcriptome of samples from longissimus dorsi muscle, perinephric fat and fat-tail of Lanzhou sheep, were subjected to RNA-Seq and 606,952 SNPs were identified overlapping with QTLs of fat traits. The latter study also suggested three potential genes (CREB1, WDR92 and ETAA1) related to fat-tail development 8 . Also, whole genome sequencing identified T gene as an important candidate gene influencing tail size in Hulunbuir short-tailed sheep 9 .…”
mentioning
confidence: 74%
“…LFTS is an endangered breed that needs protection. Compared with LFTS, STHS have smaller tails and fat accumulation ( Xu et al, 2017 ; Ma et al, 2018 ). STHS have a high reproductive capacity and show polyembryony; they grow fast and could be in oestrum at all seasons ( Kashan et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the evolution of sequencing technology, increasing sequencing is used in the identification of differential expression. A few transcriptome studies had been done to review gene expression or genetic variation profiling in livestock [4][5][6][7]. There are many studies on mRNA and long non-coding RNAs (lncRNAs) levels in the muscle from different pig breeds [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%